Exploring the Phytoconstituents, Differential Pharmacology, and Interaction with Empagliflozin of Olea europaea Leaves Extracts - Saeed, Zinah Kadhim; Al-Samydai, Ali Mahmoud; Alqaraleh, Moath; Qinna, Nidal Adel; Ghanim, Bayan Yousef; Mayyas, Amal; Al-Tawalbeh, Deniz; Alsotari, Shrouq Taiseer; Alshaer, Walhan; Al-Mamoori, Farah; Al-Halaseh, Lidia Kamal (Indian Journal of Pharmaceutical Education and Research, 2024)
Background The Olea europaea L. leaves have long been used in treating various illnesses. Its pharmacological activity based on the phytoactive constituents; therefore, optimizing the extraction process should intensify the benefits. Aim The study aimed to optimize the extraction process for O. europaea L. leaves, evaluate their antioxidant and anti-inflammatory activities, and explore their influence on the biochemical parameters of diabetic animals. Materials and Methods The differential pharmacology of the extracts and combinatorial therapy with the antidiabetic agent; empagliflozin, were explored. The aims were accomplished after several in vitro and animal studies: quantification of flavonoid and phenol content, measurement of the antioxidant activity, identification of the active constituents, and assessment of hepatic and renal functions, lipid profile, and glycemic status. In addition, molecular biology tools were used to measure the expression of the inflammatory mediators IL-6 and IL1beta. Results Findings reveal that the hydroalcoholic binary system reinforced by the sonication yields the highest polyphenol (44.40±1.414 mg/g dry extract equivalent to gallic acid) and total flavonoids (31.0700±1.202 mg/g dry extract equivalent to quercetin). Extract by the same system showed high substantial antioxidant activity. HPLC-MS/MS reveals oleuropein and its aglycon, o- and p-coumaric acid, hydroxytyrosol acetate, and betaine compounds. A significant reduction in the average weight was recorded in diabetic mice (29.79±2.88 g) compared to the control (32.61 ±2.57 g). A significant reduction in producing the inflammatory mediators IL-6 and IL1 beta was measured. Conclusion Olive leaves are a potential addition to conventional medicines to enhance the health profile of diabetic mice.
Keywords: Olive; Olea europaea L.; Diabetes; Phytoanalysis; IL-6; IL1 beta; Phytotherapy; Biodiversity; Sustainability